Naoxin’an capsules protect brain function and structure in patients with vascular cognitive impairment - Lu, Hui; Dang, Mingxi; Chen, Kewei; Shang, Huajie; Wang, Bolong; Zhao, Shaokun; Li, Xin; Zhang, Zhanjun; Zhang, Junying; Chen, Yaojing (Frontiers in Pharmacology, 2023)
Abstract Vascular cognitive dementia (VCI) is one of the most common types of dementia. Naoxin'an capsule, a traditional Chinese herbal medicine, has been used to treat VCI for a long time in the clinic. Previous studies proved that Naoxinan (NXA) capsule could ameliorate the cerebral mitochondrion deficits of VCI animals. This study aimed to investigate the protectiveness of NXA on human brain structure and function in patients with VCI. In total, 100 VCI patients were enrolled in this 24-week trial and randomly divided into NXA capsule group (n=50) and the ginkgo biloba capsules control group (n=50). Before and after the treatment, cognitive behavior tests and multimodal brain magnetic resonance imaging technology were analyzed to comprehensively evaluate the effectiveness of NXA treatment on VCI after 24 weeks. We found that the NXA group significantly improved overall cognitive ability (Alzheimer’s Disease Assessment Scale-Cognitive section, p=0.001; Mini-Mental Status Examination, p=0.003), memory (Rey-Osterrieth Complex Figure test, p<0.001) and executive function (Trail Making Test-A, p=0.024) performance after treatment compared with the control group. For brain function, the degree of centrality in the left middle frontal gyrus, right postcentral gyrus, and left supplementary motor area increased in the NXA group and decreased in the ginkgo biloba group after treatment. The fractional amplitude of low-frequency fluctuation (fALFF) of the left precentral and right superior parietal gyrus increased, and the fALFF of the right parahippocampal and left inferior temporal gyrus decreased in the NXA group after treatment. For brain structure, the gray matter density of the left postcentral gyrus increased in the NXA group after treatment, and the total volume of white matter hyperintensity showed a decreasing trend but was not statistically significant. Furthermore, the improvement effect of NXA on executive function was associated with changes in brain function. These findings suggest that the NXA capsule improved cognitive impairment and multiregional brain function, as well as gray matter structure in the postcentral gyrus.